Strategi Penerapan Manajemen Produksi Dalam Industri Beras CV. Rahma 35 Di Kabupaten Sidenreng Rappang - Mursalat, Aksal; Putri, Neva Yulaela; Qayyum, Muhammad Chaerul; Ario, Ario (MuJAgri: Musamus Journal of Agribusiness, 2023)
CV. Rahma 35 is a company in the agricultural sector focusing on rice milling and rice marketing in Sidenreng Rappang Regency. As a rice mill, production activities are the main focus of its operations. However, several obstacles are often encountered, such as rice moisture content not by standards, work accidents, machine damage, competition for grain purchase prices with other factories, and consumer complaints. This study aims to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, then formulate strategic priorities for implementing rice industry production management at CV. Rahma 35. Primary data is used through field observations and interviews, while secondary data is obtained from previous research, books, and related agencies. The results of the study indicate alternative strategies that can be considered, including increasing sales volume with promotions through social media or e-commerce, as well as efforts to increase the use of modern and conventional technology, improving performance, accuracy, and also responsibility in carrying out work and also tasks that have been given, purchase prices are adjusted to grain quality so that there are no losses and increase customer satisfaction and maintain quality and improve production processes and responsibilities are critical for a company to maintain consumer trust and satisfaction.